2014
DOI: 10.1080/08841241.2014.969798
|View full text |Cite
|
Sign up to set email alerts
|

They do not buy it: exploring the extent to which entering first-year students view themselves as customers

Abstract: While a number of scholars have discussed the pervasiveness of the conceptualization of students as customers, to date there has been limited reliable research examining the extent to which students actually view themselves as customers. Using a survey that was administered to a census of entering first-year students at a large public research university (59.8% response rate), this study shows that students do not agree with many of the educational beliefs and planned behaviors associated with a customer orien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 41 publications
2
64
0
2
Order By: Relevance
“…Burton, Xenos, Elgar, & Denny, 2013;Jenkins, Lyons, Bridgstock, & Carr, 2012); New Zealand (van der Meer, 2012); the U.S. (Saunders, 2015;Yan & Sendall, 2016;); the UK (Busse, 2013;Yorke & Vaughan, 2013); Ireland (Surgenor, 2013); Spain (Bautista, 2016;Diniz et al, 2016); and Portugal (Diniz et al, 2016). However, studies into FY students' learning experiences in Asia, especially in Taiwan, are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Burton, Xenos, Elgar, & Denny, 2013;Jenkins, Lyons, Bridgstock, & Carr, 2012); New Zealand (van der Meer, 2012); the U.S. (Saunders, 2015;Yan & Sendall, 2016;); the UK (Busse, 2013;Yorke & Vaughan, 2013); Ireland (Surgenor, 2013); Spain (Bautista, 2016;Diniz et al, 2016); and Portugal (Diniz et al, 2016). However, studies into FY students' learning experiences in Asia, especially in Taiwan, are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Students then reported their most recent grade in percent for an assessed piece of work. Next, students completed the Customer Orientation Scale (Saunders, 2014) by rating their level of agreement on a 5 point scale (1 = strongly disagree, 5 = strongly agree) with 18 statements. Minor adaptations to the wording of the statements were made so that they were appropriate for the British higher education system as opposed to the United States system.…”
Section: Methodsmentioning
confidence: 99%
“…In Tomlinson (2014), some students perceived lectures as a form of entertainment: 'sometimes you do come out of a lecture and think "well that wasn't very good" and like if you went to see a show, you'd be asking for your money back ' (p. 29). Other studies have further shown that although the majority of students do not identify strongly as consumers (Bunce et al, 2017;Saunders, 2014), those who do achieve a lower level of academic performance (Bunce et al, 2017).…”
mentioning
confidence: 97%
“…Actually, a consumerist perspective is far from universal among students even in the UK, most of whom express "mixed, almost ambivalent position on the consumerism of higher education" (Tomlinson 2016, 10, see also Saunders, 2014). Moreover, the student-as-consumer approach may fail even on its own terms, with some evidence suggesting it is associated with lower academic performance (Bunce et al 2016).…”
Section: Separation Of Cost-sharing and Marketizationmentioning
confidence: 99%